2013
DOI: 10.12816/0001501
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytokines among Women with Spontaneous Miscarriage

Abstract: The study enrolled 84 women age 15-41 years with a mean age of 25.07 ± 6.6, during the period from September 2011 till March 2012 from Basrah Hospitals, Iraq. The patients group comprised 46 women with first trimester miscarriage. The control group included 38 women with first trimester successful pregnancy with no history of miscarriage. Cytokines were measured by ELISA. There were significantly higher levels of IFN-γ, TNF-α, IL-2 and IL-10 in the aborted women as compared to the controls. In relation to IL-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
(10 reference statements)
3
13
0
Order By: Relevance
“…Increased levels of serum TNF-α and decreased IL-6 observed in the present study are in accordance with previous reports [16,17]. Similar result of IL-8 was observed in previous report by Hattori et al with disparity in levels of serum IL-6 in the present study [17].…”
Section: Discussionsupporting
confidence: 93%
“…Increased levels of serum TNF-α and decreased IL-6 observed in the present study are in accordance with previous reports [16,17]. Similar result of IL-8 was observed in previous report by Hattori et al with disparity in levels of serum IL-6 in the present study [17].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it exerts adverse effects by decreasing blood flow to the embryo resulting in blood vessel thrombosis (vascular autoamputation), interfering with the invasion of spiral arteries, endothelial dysfunction with damage to decidual vasculature, membrane matrices degradation predisposing to foetal membrane rupture. [30][31][32][33][34] In concordance with our results, an aberrant expression of TNF-α was shown to be associated with adverse placental development and function subsequently resulting in pregnancy complications. 35 In vitro studies concluded that TNF-α derived from maternal T cells stimulates apoptosis of cytotrophoblasts and syncytiotrophoblast (ST) cells in combination with interferon-gamma (IFN-γ) by inducing monocyte adhesion to ST cells to disrupt trophoblast monolayers.…”
Section: Discussionsupporting
confidence: 86%
“…The role of TNF‐α in causing miscarriage may be attributed to its potential to induce apoptosis, enhanced production of prostaglandins subsequently leading to uterine contractions. In addition, it exerts adverse effects by decreasing blood flow to the embryo resulting in blood vessel thrombosis (vascular autoamputation), interfering with the invasion of spiral arteries, endothelial dysfunction with damage to decidual vasculature, membrane matrices degradation predisposing to foetal membrane rupture 30‐34 …”
Section: Discussionmentioning
confidence: 99%
“…Chetty et al [21] demonstrated a significant relation of abortion number with women investigated with a previous miscarriage. Strobino et al [22] found that 38% of women with abortion were aborted two times due to infections. In theory, either fetal or maternal pathology could lead to recurrent spontaneous abortions [23].…”
Section: Discussionmentioning
confidence: 99%